Self-assembled mannan nanogel : cytocompatibility and cell localization - Ferreira, Sílvia A. (2012)
Amphiphilic mannan, produced by the Michael addition of hydrophobic 1-hexadecanethiol to vinyl methacrylated mannan, self-assembles in aqueous medium through hydrophobic interactions among alkyl chains. Resultant nanogel is stable, spherical, polydisperse, with 50–140 nm mean hydrodynamic diameter depending on the polymer degree of substitution, and nearly neutral negative surface charge. No cytotoxicity of mannan nanogel is detected up to about 0.4 mg/mL in mouse embryo fibroblast cell line 3T3 and mouse bone marrow-derived macrophages (BMDM) using cell proliferation, lactate dehydrogenase and Live/Dead assays. Comet assay, under the tested conditions, reveals no DNA damage in fibroblasts but possible in BMDM. BMDM internalize the mannan nanogel, which is observed in vesicles in the cytoplasm by confocal laser scanning microscopy. Confocal colocalization image analysis denotes that the entrance and exit of nanogel and FM 4-64 might occur by the same processes – endocytosis and exocytosis – in BMDM. Physicochemical characteristics, in vitro cytocompatibility and uptake of self-assembled mannan nanogel by mouse BMDM are great signals of the potential applicability of this nanosystem for macrophages targeted delivery of vaccines or drugs, acting as potential nanomedicines, always with the key goal of preventing and/or treating diseases.